Familial and genetic associations between autism spectrum disorder and other neurodevelopmental and psychiatric disorders. (20th August 2021) - Ghirardi, Laura; Kuja‐Halkola, Ralf; Butwicka, Agnieszka; Martin, Joanna; Larsson, Henrik; D'Onofrio, Brian M.; Lichtenstein, Paul; Taylor, Mark J.
Abstract : Background: Familial and genetic associations between autism spectrum disorder (ASD) and other neurodevelopmental and psychiatric disorders have been reported, sometimes with conflicting results. We estimated familial and genetic associations between ASD and nine disorder groups, and explored differences in these associations for ASD in the context of intellectual disability, epilepsy, chromosomal abnormalities, and congenital malformations. Methods: Individuals born between 1985 and 2009 living in Sweden on their seventh birthday were linked to their biological parents in order to identify different types of relatives. We retrieved information on all the disorders considered from the National Patient Register. Logistic regression was used to estimate the familial association between ASD and other neurodevelopmental and psychiatric disorders in the different groups of relatives. Structural equation modeling was used to estimate phenotypic ( r p ) and genetic associations ( r g ), as well as the contribution of genetic influences to r p . Results: The study included 2, 398, 608 individuals. Among relatives of individuals diagnosed with ASD, there was an increased risk of the disorders considered, compared to relatives of individuals who were not diagnosed with ASD. Stronger associations were detected for ASD without any additional diagnosis of intellectual disability, epilepsy, chromosomal abnormalities, and congenital malformations. The strongest genetic correlation was estimated between ASD and other neurodevelopmental disorders ( r g = 0.73; 95% CI = 0.66–0.79). Moderate genetic correlations were estimated for anxiety disorders ( r g = 0.47; 95% CI = 0.33–0.61), depression ( r g = 0.52; 95% CI = 0.37–0.66), and intentional self‐harm ( r g = 0.54; 95% CI = 0.36–0.71). Conclusions: ASD shows familial and genetic association not only with other neurodevelopmental disorders, but also with other psychiatric disorders, such as anxiety, depression, and intentional self‐harm. Family history of ASD comorbid with intellectual disability, epilepsy, congenital malformations, or chromosomal abnormalities is less related to other psychiatric disorders, potentially suggesting a different etiology for this subgroup of patients.